Nuclear reactor at home? Public acceptance of small nuclear reactors in the neighborhood - Hlavacek, Martin; Cabelkova, Inna; Pawlak, Karolina; Smutka, Lubos (Frontiers in Energy Research, 2023)
Small Nuclear Reactors (SNR) can provide climate-neutral, stable electricity and heating if located in people's neighborhoods close to people's dwellings. The extensive use of SNR would reduce capacity requirements for energy transmission systems and increase the overall stability of energy grids. However, the public fear location of SNR close to their homes. This paper hypothesizes that the public acceptance of SNR in the neighborhood is contingent upon knowledge of technology, fear of nuclear energy (NE), trust in the government, the expected increase of future electricity needs and the expected ability of renewables to cover these needs, environmental and climate concerns, and media exposure. We rely upon representative survey data from the Czech Republic (N=1013, 51,2% female, aged 18-91, M±SD: 47,7±17,6; 19,6% with higher education). Methodologically we conduct exploratory Principal Component Analysis and a series of ordinal regressions. The results suggest that the knowledge of technology, trust in the government, the preference for NE expansion, and media exposure increased the acceptance of SNR, while fear of NE decreased SNR acceptance. The perceived replaceability of conventional energy sources with renewables decreased acceptance of SNR in most cases. Surprisingly, worries about climate change reduced the support for SNR. Women accept fewer SNRs located close to their residence compared to men. More educational effort is needed in the specifics of SNR technology and the environmental effects of SNR. Media proved to be an excellent way to start.